2006
DOI: 10.1677/joe.1.06508
|View full text |Cite
|
Sign up to set email alerts
|

The effects of testosterone and oestrogen on gonadectomised and intact male rat anterior pituitary mitotic and apoptotic activity

Abstract: We have used a direct, non-immunochemical and highly accurate method to quantify the effects of testosterone and oestrogen on mitotic and apoptotic activity in the young, male rat anterior pituitary in vivo. Surgical gonadectomy resulted in a 3-fold increase in mitotic activity by the fourth post-operative day, which returned gradually to levels seen in intact animals over the subsequent 3-4 weeks. Both a single dose of Sustanon, a mixture of long-acting testosterone esters in arachis oil, and the same dose di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 34 publications
1
37
1
Order By: Relevance
“…The activation of cell proliferation necessarily primes the cellular apoptotic program that, unless abrogated by appropriate survival signals, removes the affected cell [37]. It has been reported that dexamethasone or testosterone treatments after adrenalectomy or gonadectomy induce mitotic and apoptotic activity in the anterior pituitary [38,39]. Our results suggest that chronic estrogen treatment may trigger both proliferation and apoptosis of anterior pituitary cells, processes closely linked to each other.…”
Section: Discussionmentioning
confidence: 58%
“…The activation of cell proliferation necessarily primes the cellular apoptotic program that, unless abrogated by appropriate survival signals, removes the affected cell [37]. It has been reported that dexamethasone or testosterone treatments after adrenalectomy or gonadectomy induce mitotic and apoptotic activity in the anterior pituitary [38,39]. Our results suggest that chronic estrogen treatment may trigger both proliferation and apoptosis of anterior pituitary cells, processes closely linked to each other.…”
Section: Discussionmentioning
confidence: 58%
“…Testosterone has been shown to increase mitotic activity in pituitary glands of rats and to increase PRL levels in men [12,22]. Deterioration of visual field defects and increased tumor size has been reported in men with macroprolactinoma receiving testosterone replacement therapy [23].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens generated locally by aromatization may be involved in the activation of anterior pituitary mitotic activity [13,27]. Therefore, increased aromatase expression may lead to the growth of pituitary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment group received letrozole orally (Femara, Novartis group, 1 mg/kg per day dissolved in 10% gelatin; Nolan & Levy 2006). The gelatin preparation was consumed avidly by the rats.…”
Section: Interventionmentioning
confidence: 99%